Nikah Mut'ah Dalam Fiqh dan Perundang-Undangan Indonesia - Halim, Abd. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2002)
There are differences of opinion among Muslims about the validity of mut'ah marriage (temporary marriage). Some permit it and others do not. The Syi'ah Imamiyyah allows it, whereas the majority of Muslims (Sunni, Syi'ah Zaidiyyah and Syi'ah Isma'iliyyah) do not. This paper studies the views of these two groups, as well as the argumentation they use, and also looks at which view is closer in spirit to the marriage law in Indonesia. After analysing the two arguments, can be concluded that the stronger argument is that of the majority of ulama who do not allow mut'ah marriage. Meanwhile in terms of Indonesian marriage law, mut'ah marriage is not in accordance with the goals and idealism of the family as a body and soul bond to create a household that is sakinah, mawaddah and rahmah.